Pengaruh Zat Alelopati Dari Pohon Akasia, Mangium, Dan Jati Terhadap Pertumbuhan Semai Akasia, Mangium, Dan Jati - Novia Ekayanti; Indriyanto Indriyanto; Duryat Duryat (Jurnal Sylva Lestari, 2015)
Allelopathy is the compound released by the plants to the environtment where actualy another plants is living in. The purpose of this research were to find out the effect of allelopathy which came from earpod wattle (Acacia auriculiformis), black wattle (Acacia mangium), and teak (Tectona grandis) to the seedlings plants of earpod wattle, black wattle, and teak, and also to find out the effect of allelopathy above mentioned that had the weakest effect. This research was designed based on factorial in a complete random design. Factor I was the seedlings which consist of earpod wattle, black wattle, and teak, while factor II was the allelopathy which consists of non allelopathy was used, the use of allelopathy from the extraction of earpod wattle leaves, the extraction of black wattle leaves, and the extraction of teak leaves. The variable that was observed were seedlings height increasing, seedlings stem diameter increasing, number of leaves increasing, and living percentage of the seedlings. This observation data was tested by Bartlett test to know the homogenity of variance. Then it was analyzed by analysis of variance, then it is continually tested by least significant difference test. All the counting were done at 5% significant level. The result of this research showed that allelopathy which one came from earpod wattle, black wattle, and teak were not different effect for seedlings from allelopathy source in the same species. The giving of black wattle allelopathy had significant different effect in height earpod wattle seedlings. That also the giving of teak allelopathy had significant different effect in height black wattle seedlings. The earpod wattle allelopathy had significant different effect in diameter of stem earpod wattle, black wattle, and teak seedlings. Keywords: allelopathy, extraction of earpod wattle, black wattle, and teak, seedlings growth